Long-Term Projection of Transport-Related Social Cost of Greenhouse Gas Emissions in Qatar - Maryam Al-Jabir (19171159) (2024)
The transportation sector has garnered significant attention recently due to its substantial impact on greenhouse gas (GHG) emissions, which have contributed to global warming and adversely impacted human health and the environment. This study estimates the social cost of carbon (SCC) in Qatar pertaining to road transportation, explicitly focusing on the greenhouse gases (GHGs) of carbon dioxide, methane, and nitrous oxide for the years 2030, 2040, and 2050. The Low Emissions Analysis Platform (LEAP) was utilized to formulate various scenarios: (1) a public transport scenario in comparison to the baseline scenario; (2) a scenario with improved fuel economy in comparison to the baseline scenario; and (3) a scenario with improved fuel economy in comparison to the public transport scenario. Once the scenarios were developed, the emission reduction values were derived. Subsequently, the Social Cost of Carbon Explorer tool was employed to assess the SCC for each gas. According to the study findings, when comparing the public transport scenario with the baseline scenario, it was observed that the total SCC benefit in 2030, 2040, and 2050 would amount to USD 380,005,861. Furthermore, when comparing the scenario in which fuel economy is improved to the baseline scenario, the total SCC benefit would amount to USD 3,363,559. In conclusion, upon comparing the scenario of improved fuel economy with that of public transportation, it is determined that the total SCC benefit would amount to USD 5,980,883. The calculation of the SCC is expected to provide valuable insights for decision making pertaining to the economic implications of different strategies to mitigate greenhouse gas emissions in Qatar. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su16020536